PROJECT BASED LEARNING MODULE IN THE SCREEN PRINTING COURSE AT THE INDONESIAN INSTITUTE OF THE ARTS PADANG PANJANG - Mulyadi; Miswar , Vanesha; Ade Putra; Miswar (PT. Antis International Publisher, 2025)
Objective: This research is motivated by efforts to achieve learning outcomes for students who face various learning challenges, such as the need to improve creativity in solving problems during the learning process. These challenges include a lack of references and inadequate learning resources, which impact students' ability to develop problem-solving thinking, and so far, students still rely on the material explained by the lecturer at the beginning of the course meeting, without any learning resources or teaching materials as a guide in implementing the practice. Method: This type of research is development research or known as Research and Development (R & D), and this research approach uses the ADDIE approach which consists of five research stages, namely: Analyze, Design, Develop, Implement and Evaluate, while validation was carried out by three expert validators, each on the aspects of material, design and language, and each validator was asked to fill out the assessment instrument using a Likert scale of 1–5 against a number of indicators that had been prepared. Result: The recapitulation results showed that the material validator gave a score of 41 out of a total maximum score of 45 with a percentage of (91.11%), the design validator gave a score of 44 out of a total maximum score of 50 with a percentage of (88%) and the language validator gave a score of 46 out of a total maximum score of 50 with a percentage of (92%), and the results of the practicality data analysis of the learning module were at a practicality level of 88.56% with an interpretation category that was very practical to use in the learning process. Novelty: These findings indicate that the developed module not only meets expert validation criteria but also achieves a very practical level for implementation, which highlights the novelty of providing effective and validated teaching materials that address the lack of references and inadequate resources in student learning.